Analisis Hukum atas Tindak Pidana Penipuan Melalui Rekaman Suara Berbasis Kecerdasan Buatan (AI) dalam Perspektif Kejahatan Ekonomi - Richo Ardi Darmawan (CV Rewang Rencang, 2025)
Fraud through voice recordings based on artificial intelligence (AI) is increasingly widespread and causes significant economic losses. This study analyzes the legal aspects of such fraud crimes from the perspective of economic crime by reviewing existing regulations and law enforcement. The results indicate that current regulations are not fully capable of anticipating the development of AI technology in voice fraud. In conclusion, there is a need to improve regulations and adapt law enforcement to technology to effectively prevent and handle this crime.